Patients with COVID‐19 who experience a myocardial infarction have complex coronary morphology and high in‐hospital mortality: Primary results of a nationwide angiographic study. Issue 3 (27th April 2021) - Abizaid, Alexandre; Campos, Carlos M.; Guimarães, Patrícia O.; Costa, José de Ribamar; Falcão, Breno A. A.; Mangione, Fernanda; Caixeta, Adriano; Lemos, Pedro A.; de Brito, Fabio S.; Cavalcante, Ricardo; Bezerra, Cristiano Guedes; Cortes, Leandro; et al.
Abstract: Objectives: We aimed to explore angiographic patterns and in‐hospital outcomes of patients with concomitant coronavirus disease‐19 (COVID‐19) and myocardial infarction (MI). Background: Patients with COVID‐19 may experience MI during the course of the viral infection. However, this association is currently poorly understood. Methods: This is a multicenter prospective study of consecutive patients with concomitant COVID‐19 and MI who underwent coronary angiography. Quantitative and qualitative coronary angiography were analyzed by two observers in an independent core lab. Results: A total of 152 patients were included, of whom 142 (93.4%) had COVID‐19 diagnosis confirmation. The median time between symptom onset and hospital admission was 5 (1–10) days. A total of 83 (54.6%) patients presented with ST‐elevation MI. The median angiographic Syntax score was 16 (9.0–25.3) and 69.0% had multi‐vessel disease. At least one complex lesion was found in 73.0% of patients, 51.3% had a thrombus containing lesion, and 57.9% had myocardial blush grades 0/1. The overall in‐hospital mortality was 23.7%. ST‐segment elevation MI presentation and baseline myocardial blush grades 0 or 1 were independently associated with a higher risk of death (HR 2.75, 95%CI 1.30–5.80 and HR 3.73, 95%CI 1.61–8.61, respectively). Conclusions: Patients who have a MI in the context of ongoing COVID‐19 mostly present complex coronary morphologies, implying a background of prior atherosclerotic disease superimposed on a thrombotic milieu. The in‐hospital prognosis is poor with a markedly high mortality, prompting further investigation to better clarify this newly described condition.